Investigation of Tissue Components Impacts on Dose Enhancement Factor Using Monte Carlo Code - AL-suhbani, M. N.; Baghous, N. E. H.; Serag, S.; EL Mahjoub, C.; Ait-Mlouk, L.; Zia, A.; Hamid, B.; Azougagh, M. (National Research and Innovation Agency, 2024)
Despite the progress of science in cancer treatments and radiotherapy improvements, there are still several side effects that occur during tumors treatment, particularly on healthy tissues surrounded tumors. Newer treatment methods are being explored lately, one of which is the use of nanoparticles, wherein the tumor is injected with gold nanoparticles. Its aim is to enhance tumor sensitivity to radiation and reduce radiation damage to healthy tissues. Tissue type may play an effective role in enhancing the dose being received under the use of nanoparticles. This study aims to find the effect of different tissue components on dose enhancement factor through MCNP6 and GATE simulations, as well as to accurately compare the simulation results of these two code packages for dose enhancement factors. A 125I brachytherapy source was simulated in phantoms for five tissues or materials (adipose tissue, breast tissue, soft tissue, water, and brain tissue). MCNP6 simulation code was validated by comparing its results with a previous study by Cho et al. Gold nanoparticles were injected as a mixture at a concentration of 7 mg/g into tissues inside a tumor. MCNP6 and GATE simulation results were compared. It was estimated from MCNP simulations that the highest radiation dose enhancement of 2.34 occurs in adipose tissue while lowest dose enhancement of 1.69 is in brain. In comparison, from GATE results, the estimates were that the highest value of dose enhancement factor also occurred in adipose tissue at 2.01, and the lowest value in brain at 1.48. The comparison between two codes suggest that they are compatible with the percentage difference in all tissues being less than 15 %. This study confirms that both MCNP6 and GATE codes could calculate DEF for different tissues under irradiation from a low-energy source.